Determinants of cashless society, a case of Inyati Mine in Rusape - Chaparadza, Sherpherd (goodwood publishing, 2024)
Purpose: This study aimed to identify the variables affecting the Inyati community in Inyati Mine's adoption of mobile money. Research Methodology: A descriptive research design was employed using a stratified random sampling technique. Results: A target population of 300 households was contacted, and the research concluded that some rural residents find it difficult to access mobile money because of their inferior technological skills, while others believe that network coverage is limited to certain areas of the community, and rural residents are adopting mobile money more slowly than their urban counterparts. Limitations: The study was restricted to a small community; hence, the findings may not be applicable to a wider community. Recommendations: This research recommends that network operators ensure network consistency and wide coverage if potential members of the communities are to be included in the mobile wallet. It further recommends some improvements to mobile app systems to remove application complexity; it recommends that mobile money operators partner with international remitting agencies to include excluded groups of potential customers who receive their income from abroad. It also recommends abolishing end-to-end transaction fees to reduce overall transaction costs.